Functional Disorders: Rectocele - Mustain, W. Conan (Clinics in Colon and Rectal Surgery, 2017)
Rectoceles are a very common finding in patients, and symptoms most commonly include pelvic pain, pressure, or difficulty with passing stool. However, there are often other associated pelvic floor disorders that accompany rectoceles, making the clinical significance of it in an individual patient often hard to determine. When evaluating a patient with a rectocele, a thorough history and physical exam must be conducted to help delineate other causes of these symptoms. Treatment consists of addressing other defecatory disorders through various methods, with surgery reserved for select cases in which obstructed defecation is well documented.
Keywords: rectocele; pelvic floor; posterior compartment; obstructed defecation syndrome